Findings in Patients From Benin With Osteomyelitis and Polymerase Chain Reaction–Confirmed Mycobacterium ulcerans Infection. (21st July 2014) - Pommelet, Virginie; Vincent, Quentin B.; Ardant, Marie-Françoise; Adeye, Ambroise; Tanase, Anca; Tondeur, Laura; Rega, Adelaide; Landier, Jordi; Marion, Estelle; Alcaïs, Alexandre; Marsollier, Laurent; Fontanet, Arnaud; et al.
Abstract : Mycobacterium ulcerans can lead to severe forms of infections, including osteomyelitis. This study identified patients with lesions both adjacent to and distant from skin lesions as well as those with no apparent history of skin lesions, here termed exclusive osteomyelitis . Abstract: Background.   Mycobacterium ulcerans is known to cause Buruli ulcer (BU), a necrotizing skin disease leading to extensive cutaneous and subcutaneous destruction and functional limitations. However, M. ulcerans infections are not limited to skin, and osteomyelitis, still poorly described in the literature, occurs in numerous young patients in Africa. Methods.  In a retrospective matched case-control study conducted in a highly endemic area in Benin, we analyzed demographic, clinical, biological, and radiological features in all patients with M. ulcerans infections with bone involvement, identified from a cohort of 1257 patients with polymerase chain reaction–proved M. ulcerans infections. Results.  The 81 patients studied had a median age of 11 years (interquartile range, 7–16 years) and were predominantly male (male–female ratio, 2:1). Osteomyelitis was observed beneath active BU lesions (60.5%) or at a distance from active or apparently healed BU lesions (14.8%) but also in patients without a history of BU skin lesions (24.7%). These lesions had an insidious course, with nonspecific clinical findings leading to delayed diagnosis. A comparison with findings in 243 age- and sex-matched patients with BU without osteomyelitis showed that case patients were less likely to have received BCG immunization than controls (33.3% vs 52.7%; P = .01). They were also at higher risk of longer hospital stay (118 vs 69 days; P = .001), surgery (92.6% vs 63.0%; P = .001), and long-term crippling sequelae (55.6% vs 15.2%; P < .001). Conclusions.  This study highlighted the difficulties associated with diagnosis of M. ulcerans osteomyelitis, with one-fourth of patients having no apparent history of BU skin lesions, including during the current course of illness. Delays in treatment contributed to the high proportion (55.6%) of patients with crippling sequelae.